2012
DOI: 10.1016/j.jss.2011.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Subnormothermic Machine Perfusion at Both 20°C and 30°C Recovers Ischemic Rat Livers for Successful Transplantation

Abstract: Background Utilizing livers from donors after cardiac death could significantly expand the donor pool. We have previously shown that normothermic (37°C) extracorporeal liver perfusion significantly improves transplantation outcomes of ischemic rat livers. Here we investigate whether recovery of ischemic livers is possible using sub-normothermic machine perfusion at 20°C and 30°C. Methods Livers from male Lewis rats were divided into five groups after 1 h of warm ischemia (WI): (1) WI only, (2) 5 h of static … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 33 publications
0
50
0
Order By: Relevance
“…At the same time, it provides a decreased oxygen demand in comparison to normothermic perfusion settings which provides additional safety against ischemic injury. In general, perfusion temperatures above 30 °C have shown to minimize cold ischemic injury and provide sufficient metabolic activity 31 .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it provides a decreased oxygen demand in comparison to normothermic perfusion settings which provides additional safety against ischemic injury. In general, perfusion temperatures above 30 °C have shown to minimize cold ischemic injury and provide sufficient metabolic activity 31 .…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Although recent data from animal models and (discarded) human donor livers have provided promising results suggesting that endischemic MP has relevant protective effects on the bile ducts of donation after cardiac death (DCD) liver grafts, the most optimal perfusion temperature during end-ischemic MP has not been investigated. [7][8][9][10][11][12][13][14][15][16][17] The aim of this study was, therefore, to assess the optimal perfusion temperature during end-ischemic oxygenated MP for protection of the large bile ducts against I/R injury in a DCD rat liver model.…”
mentioning
confidence: 99%
“…66 Likewise, several other groups have suggested that subnormothermic machine perfusion can recover and allow transplant of ischemic livers with promising results. 64,67 Notably, successful preservation of rat livers for up to 4 days can be achieved using supercooling and subsequent subnormothermic machine perfusion. 68 This method has the potential to prolong transport of DCD livers by 3-to 4-fold.…”
Section: Future Considerationsmentioning
confidence: 99%